GERAKAN ANTI KORUPSI MALANG CORRUPTION WATCH - yusuf adam hilman; Herlambang Septa Nugraha (Department of Sociology, Faculty of Social and Political Science, Universitas Padjadjaran, 2018)
Journey of the indonesia cannot be separated from the whose name corruption, various problems corruption then make a nation it tries to with very hard to do the eradication of corruption, then now kpk, the commission would grow up and incarnate as a power terlembaga, however kpk but many that blocks, so that his movement often in politician, in addition problems arise related the area of that causes limited kpk in running tasks and functions. Then institutions here needed in regions have motion based in society to be opposition from government in the fight against corruption the , one of which is unfortunate corruptions watch that is unfortunate highway , to attract football to scrutinize about lunge mcw as of a motion social , this research use the model descriptive qualitative , with data source of interviews and documentation. MCW is non-governmental organizations which has grown and developed social as of a motion that which appears or present of former activist in the era of reformasi, mcw use 3 strategies in efforts to eradicate corruption namely, prevention, law enforcement, anti-corruption education.